2022
DOI: 10.1177/07487304221122662
|View full text |Cite
|
Sign up to set email alerts
|

Time for Exercise? Exercise and Its Influence on the Skeletal Muscle Clock

Abstract: Circadian rhythms drive our daily behaviors to coincide with the earth’s rotation on an approximate 24-h cycle. The circadian clock mechanism present in nearly every cell is responsible for our circadian rhythms and is comprised of a transcriptional-translational feedback loop in mammals. The central clock resides in the hypothalamus responding to external light cues, whereas peripheral clocks receive signals from the central clock and are also sensitive to cues from feeding and activity. Of the peripheral clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 88 publications
1
5
0
Order By: Relevance
“…Experimental studies have indicated that superior anaerobic exercise performance in the afternoon vs. morning can be significantly attenuated by anaerobic exercise training in the morning (6 a.m.) ( Souissi et al, 2002 ; Chtourou and Souissi, 2012 ), and other research has indicated a greater improvement in anaerobic threshold in the morning and afternoon following training in the morning and afternoon, respectively ( Hill et al, 1989 ). These results are consistent with compelling evidence that the time of day of exercise can shift the skeletal muscle clock ( Martin and Esser, 2022 ) which could impact performance.…”
Section: Introductionsupporting
confidence: 89%
“…Experimental studies have indicated that superior anaerobic exercise performance in the afternoon vs. morning can be significantly attenuated by anaerobic exercise training in the morning (6 a.m.) ( Souissi et al, 2002 ; Chtourou and Souissi, 2012 ), and other research has indicated a greater improvement in anaerobic threshold in the morning and afternoon following training in the morning and afternoon, respectively ( Hill et al, 1989 ). These results are consistent with compelling evidence that the time of day of exercise can shift the skeletal muscle clock ( Martin and Esser, 2022 ) which could impact performance.…”
Section: Introductionsupporting
confidence: 89%
“…Light is the dominant environmental cue for the SCN and light therapy is reported to improve the sleep quality among patients with neurodegenerative disorders 15,16 , to decrease fatigue symptoms among cancer patients 17,18 , and to improve circadian misalignment in Space 19,20 . Besides light, the circadian system is also sensitive to other Zeitgebers related to meal timing (e.g., fasting and caloric restriction 21 ) or to physical exercise [22][23][24] . At the molecular level, circadian rhythms in gene and protein expression are generated via transcriptional-translational feedback loops (TTFL) where Brain and muscle ARNTL-like 1 (BMAL1; also known as ARNTL) forms a heterodimer with Circadian locomotor output cycles kaput (CLOCK) and regulates the transcriptional activation of Period 1/2/3 (PER 1/2/3), and Cryptochrome 1/2 (CRY 1/2), which in turn inhibit BMAL1-CLOCK mediated transcription 25 .…”
Section: Introductionmentioning
confidence: 99%
“…However, it is unclear whether the time of day of exercise is important for optimizing health. It has been hypothesized in a recent review that exercise timing could be a promising approach in metabolic diseases, because skeletal muscle clocks are very sensitive to exercise and also involved in the expression of glucoregulatory genes [ 88 ]. As shown by this systematic review, to date only few studies have examined this issue.…”
Section: Discussionmentioning
confidence: 99%